2019
DOI: 10.1149/2.0361909jes
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Mimic Motion of 3D-Printed Gel Structures Dispersed with Magnetic Particles

Abstract: The authors have proposed a fabrication process of "4D printer" for magnetic soft actuators. In this paper, we applied this 4D printer to bio-mimic field and show some examples using a gel material dispersed with magnetic powder. 4D printer is a recently developed process that can print out not only a 3-dimensional structure but also print deformations of the printed structure at the same time. We employed a UV-curable gel material. The material could be used in the same manner as the conventional 3D-printing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…In fact, previous studies have demonstrated magnetic soft robots shaped as rectangular thin films (without cilia or legs) that exhibit net motion precisely due to the undulating wavy deformation of the soft body. 2 , 30 However, the locomotion speed of our ciliated metachronal robot is substantially larger than that of the film-shaped robot demonstrated by Shinoda et al, 30 as detailed in Section S9 . This suggests that the contribution of the wavy deformation to the total locomotion is minor relative to the effect of the metachronal motion of the cilia, acting as the robot’s legs.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…In fact, previous studies have demonstrated magnetic soft robots shaped as rectangular thin films (without cilia or legs) that exhibit net motion precisely due to the undulating wavy deformation of the soft body. 2 , 30 However, the locomotion speed of our ciliated metachronal robot is substantially larger than that of the film-shaped robot demonstrated by Shinoda et al, 30 as detailed in Section S9 . This suggests that the contribution of the wavy deformation to the total locomotion is minor relative to the effect of the metachronal motion of the cilia, acting as the robot’s legs.…”
Section: Resultsmentioning
confidence: 67%
“…The mechanism of creating metachronal cilia can be summarized into two categories: (i) applying different forces to each cilium within an array of cilia 23 , 26 , 27 and (ii) designing an array of cilia with different responses to a uniformly applied stimulus such as a uniform magnetic field. 19 , 27 30 The latter is beneficial due to its much simpler actuation method. The fabrication approaches presented in previous papers, however, are either time-consuming because complex assembly steps are needed 28 , 29 or they are based on expensive raw materials, costly processes, or complex actuation devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 The technique has also been implemented to fabricate polymer based soft actuators; for example, actuators based on stimuli responsive elastomers for softrobotic applications and magnetic soft actuators showcasing biomimicry were fabricated through 4D printing technique. 12,13 Similarly, hydrogel based, shape morphing structures were 4D printed to produce reversible deformations for soft actuation applications. 14,15 However, these 3D/4D printing techniques were limited to millimeter sizes only, and to extend the scalability of this process, we are demonstrating the use of 3D printing process to fabricate even smaller structures in the micrometer domain.…”
Section: Introductionmentioning
confidence: 99%
“…b) Orientation of ferromagnetic particles in the composite ink by applying an external magnetic field around the nozzle during printing process (up) and two-dimensional printed structures with programmed multiple magnetic domains exhibiting 3D shape change on exposure to an applied magnetic field (down),[175]. c) Setting magnetic anisotropy during the printing process to fabricate a multidomain structure acting as a worm-like soft actuator under the influence of a rotational magnetic field,[176].…”
mentioning
confidence: 99%